Perforator Propeller Flap for Oncologic Reconstruction of Soft Tissue Defects in Trunk and Extremities. Issue 4 (October 2016) - Yu, Shengji; Zang, Mengqing; Xu, Libin; Zhao, Zhenguo; Zhang, Xinxin; Zhu, Shan; Chen, Bo; Ding, Qiang; Liu, Yuanbo
Abstract : Background: Defects after soft tissue sarcoma resection are usually managed by myocutaneous flaps or free flaps. However, harvesting muscle will cause functional morbidities, and some regions lack reliable recipient vessel. Our purpose is to use various perforator propeller flaps for oncologic reconstruction. Methods: Between 2008 and 2014, 33 perforator propeller flaps were performed in 24 patients to reconstruct the defects after tumor resection in trunk and extremities. Fifteen patients underwent tumor resection previously. Thirteen patients underwent adjuvant radiotherapy or chemotherapy. Flaps based on perforators adjacent to the lesions were raised and rotated in propeller fashion to repair the defects. Results: Twenty-seven flaps were based on perforators of known source vessels, and 6 were harvested in freestyle fashion. The defects were repaired with 2 flaps in 4 patients and 3 flaps in 2 patients. The mean skin paddle dimension was 8.36 cm in width and 20.42 cm in length. The mean degree of flap rotation was 158.79°. Complications include partial necrosis of 6 flaps in 5 cases and venous congestion of 1 flap. In these 6 patients, 3 underwent adjuvant radiotherapy. The donor sites were primarily closed in 21 patients and skin grafted in 3 patients. No functional loss related to flap harvesting was recognized. Conclusions: The perforator propeller flaps can be used to manage the medium defects in extremities and large defects in torso after soft tissue sarcoma resection. They avoid the sacrifice of the underlying muscle and eliminate the concerns of the unavailability of recipient vessels. The perforator propeller flaps provide flexible options for versatile oncologic reconstruction in trunk and extremities. However, the impact of radiotherapy on the viability of the flaps for local reconstruction needs further investigation.